New challenges in vaccination policies: the role of General Practitioners - Signorelli, Carlo; Priori, Marta; Odone, Anna; Vezzosi, Luigi; Colucci, Maria Eugenia; Affanni, Paola; Veronesi, Licia; Maio, Tommasa (Acta Biomedica Atenei Parmensis, 2020)
The phenomenon of “Vaccine Hesintacy” and the consequent decrease in vaccination coverage with the re-ignition of some epidemic outbreaks has led Italian national and regional authorities to set a new vaccination plan (PNPV 2017-19) and even coercive measures such as the the Law n.119/2017. In addition, there have been initiatives by scientific societies also in order to increase involvement of professionals in information and education campaigns. Among the professional figures involved, the general practitioners represents the starting point from which to regain the citizen’s trust. This article assesses their important role in the implementation of vaccination policies in Italy by identifying the essential points of the campaigns carried out on their patients.